Adult plant resistance to leaf rust and stem rust of wheat in a newly developed recombinant inbred line population. Issue 2 (15th March 2018) - Figlan, Sandiswa; Terefe, Tarekegn G; Shimelis, Hussein; Tsilo, Toi J
Abstract : Leaf rust caused by Puccinia triticina and stem rust by P. graminis f. sp. tritici are the most destructive diseases of wheat ( Triticum aestivum L.), resulting in substantial yield losses globally. A continuous search for new sources of effective rust resistance genes is necessary to develop improved cultivars with durable resistance. This study aimed to investigate inheritance of adult-plant resistance in a recombinant inbred line (RIL) population of a cross between wheat cultivars 'Popo' and 'Kariega', and to identify breeding lines possessing both leaf rust and stem rust resistance. A panel of 179 RILs, two parental cultivars and three checks were evaluated in South Africa at two localities, Cedara and Tygerhoek, in 2014 and 2015. Disease response ranged from highly resistant to highly susceptible. Analysis of variance indicated highly significant ( p  < 0.001) differences among the RILs for both diseases across the testing environments. Broad-sense heritability estimates were 0.53 and 0.77 for leaf rust and stem rust, respectively. Twenty-six RILs were selected showing significantly higher levels of resistance to both pathogens. The moderate to high heritability estimates for leaf rust and stem rust resistance favours the use of the newly developed RILs for resistance breeding against the two diseases.